Effect of changes in end‐tidal carbon dioxide tension on oral tissue blood flow during dexmedetomidine infusion in rabbits. (29th December 2014) - Okada, Reina; Matsuura, Nobuyuki; Kasahara, Masataka; Ichinohe, Tatsuya
<x xml:space="preserve">Abstract</x> A decrease in arterial carbon dioxide tension induces an increase in masseter muscle blood flow and a decrease in mandibular bone marrow blood flow during general anesthesia. In addition, dexmedetomidine infusion reduces oral tissue blood flow. In this study we investigated how end‐tidal carbon dioxide tension (ET‐CO2) changes influence on oral tissue blood flow during continuous dexmedetomidine infusion in rabbits. Eleven male Japan White rabbits were anesthetized with sevoflurane. Then, ET‐CO2 was set at 30 mmHg and adjusted to 40 and 60 mmHg, and heart rate, systolic blood pressure, diastolic blood pressure, mean arterial pressure, common carotid artery blood flow, mandibular bone marrow blood flow, masseter muscle blood flow, and blood flow in other oral tissues were measured. Following this, the ET‐CO2 was returned to 30 mmHg and dexmedetomidine was infused over 60 min. The measurements were repeated. Most parameters increased, regardless of whether or not dexmedetomidine was present, and heart rate and masseter muscle blood flow decreased in an ET‐CO2‐dependent manner. Dexmedetomidine infusion suppressed ET‐CO2‐dependent masseter muscle blood flow change. Masseter muscle blood flow during ET‐CO2 at 30 mmHg with dexmedetomidine was the same as that during ET‐CO2 at 40 mmHg without dexmedetomidine. Our findings suggest that dexmedetomidine infusion and slight hypocapnia under general anesthesia suppress an increase in masseter muscle blood flow as well as reducing mandibular bone marrow blood flow. These results may be of significance for decreasing bleeding during oral and maxillofacial surgery.